PENGARUH PENGALAMAN KEUANGAN DAN TINGKAT PENDAPATAN TERHADAP PERILAKU KEUANGAN KELUARGA DI DESA YOSOWILANGUN KECAMATAN MANYAR GRESIK - Wasti Reviandani (Jurnal Manajerial, 2019)
This study analyzes the effect of financial experience and income level on family financial behavior. This research took place in Yosowingaun village in Manyar Gresik sub-district, which was inhabited by 9490 residents with economic activities including trading, farming, or being employees. The samples taken from this study were 38 people using multiple linear regression analysis, the results of this study that Financial experience and the level of opinion of citizens significantly influence family financial behavior in Yosowilangun village, Manyar Gresik sub-distric